Anima de Wajdi Mouawad: El trauma y la violencia de la guerra en la construcción identitaria del exiliado - Contreras Pérez, Marta (Anales de Filología Francesa, 2021)
The main objective of this article is the critical study of the novel Anima by the Lebanese born and naturalised Canadian writer Wajdi Mouawad (1968-). This self-fictional work, characterized by a polyphony of animal storytellers, seduces and discomforts the reader as he or she witnesses atrocious and savage acts: rape, murder, torture and war. Each chapter brings us closer to the consequences of a linguistic, ideological, cultural and geographical exile derived from the Lebanese civil war that the author himself suffered during his childhood. Mouawad, considered a committed writer, reflects on the identity of the exile: an individual who has been a victim of loss, loneliness, violence and trauma.